SIKAP PERAWAT DALAM PROSES TIMBANG TERIMA DI RSUD DR. R. SOSODORO DJATIKUSUMO BOJONEGORO ATTITUDES OF NURSES IN THE PROCESS OF HANDOVER IN DR. R. SOSODORO DJATIKUSUMO BOJONEGORO - MAFTUKHIN, AHMAD; NURUL, SITI; P, ANGGA (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2016)
Handover in RSUD Bojonegoro there is 45% of nurses in hospitals Bojonegoro not be able to accept what has been well documented and passed around by a nurse in the office earlier. The purpose of this study was to identify the attitudes of nurses in the process handover in RSUD dr. R. Sosodoro Djatikoesoemo Bojonegoro.             The study design used is descriptive. The approach used in the study is survey. The total sample used is  59 respondents who are nurse in wijaya kusuma, bougenvil, melati, flamboyan and sakura room. Variable used single variable, namely the attitude of nurses in the process of handover. then done editing, coding, scoring, and tabulating then be deduced by using percentage.             The results of the research that there are obtained 51% of the respondents stated to have positive attitude/Favorable while there are 49% of respondents expressed negative attitude/Unfavorable.                The conclusion of this study in RSUD dr. R. Sosodoro Djatikusumo Bojonegoro that more than most of the respondents have positive attitude/favorable. To handover  is perfect as the need to set up a special team to weigh the supervisor received and way to give gifts to nurses who have good performance and professional.